Handbook of research on expanding business opportunities with information systems and analytics - Jamil, George Leal, 1959- (Business Science Reference, 2019)
"This book explores expanding business opportunities with information systems and analytics. It also examines how the demand for the integration of all resources, managerial principles, processes and people development fit in the theoretical base of information systems"--